HECW1 induces NCOA4-regulated ferroptosis in glioma through the ubiquitination and degradation of ZNF350 - Yuancai Lin; Hailong Gong; Jinliang Liu; Zhiwen Hu; Mingjun Gao; Wei Yu; Jing Liu (Cell Death and Disease, 2023)
Abstract Tumor suppression by inducing NCOA4-mediated ferroptosis has been shown to be feasible in a variety of tumors, including gliomas. However, the regulatory mechanism of ferroptosis induced by NCOA4 in glioma has not been studied deeply. HECW1 and ZNF350 are involved in the biological processes of many tumors, but their specific effects and mechanisms on glioma are still unclear. In this study, we found that HECW1 decreased the survival rate of glioma cells and enhanced iron accumulation, lipid peroxidation, whereas ZNF350 showed the opposite effect. Mechanistically, HECW1 directly regulated the ubiquitination and degradation of ZNF350, eliminated the transcriptional inhibition of NCOA4 by ZNF350, and ultimately activated NCOA4-mediated iron accumulation, lipid peroxidation, and ferroptosis. We demonstrate that HECW1 induces ferroptosis and highlight the value of HECW1 and ZNF350 in the prognostic evaluation of patients with glioma. We also elucidate the mechanisms underlying the HECW1/ZNF350/NCOA4 axis and its regulation of ferroptosis. Our findings enrich the understanding of ferroptosis and provide potential treatment options for glioma patients.